2008
DOI: 10.1056/nejmoa0707427
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Events during World Cup Soccer

Abstract: Viewing a stressful soccer match more than doubles the risk of an acute cardiovascular event. In view of this excess risk, particularly in men with known coronary heart disease, preventive measures are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
242
2
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(274 citation statements)
references
References 22 publications
7
242
2
10
Order By: Relevance
“…Although the psychological upheaval caused by earthquakes and wars cannot be equated with the stress caused by sporting events, it is likely that sporting events increase the risk of cardiovascular events. Several studies have found that soccer matches are related to increased cardiac emergencies and myocardial infarction 7, 8. Conversely, mortality from myocardial infarction decreased in France after a World Cup final in 1998 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the psychological upheaval caused by earthquakes and wars cannot be equated with the stress caused by sporting events, it is likely that sporting events increase the risk of cardiovascular events. Several studies have found that soccer matches are related to increased cardiac emergencies and myocardial infarction 7, 8. Conversely, mortality from myocardial infarction decreased in France after a World Cup final in 1998 9.…”
Section: Introductionmentioning
confidence: 99%
“…Watching sumo is popular among elderly people 11. Acute mental stress increases the risk of a variety of cardiovascular events 7, 8, 12. Since sumo is fierce struggle which causes increased emotions in spectators, it is possible that watching sumo matches increases the risk of cardiovascular events, particularly among elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…The recently published and already celebrated analysis of coronary heart disease clinical presentations in German nationals in Munich during the 2006 Fédération Internationale de Football Association World Cup provides a telling example in demonstrating a dose-response relationship of the level of acute mental stress (judged from the closeness of the contest and the particular relevance of the result to Germany), and presumably sympathetic nervous activation, to cardiac events. 2 The case is no less strong that chronic sympathetic activation is similarly adverse. In patients with heart failure, the cardiac sympathetic outflow is preferentially and often very highly activated.…”
mentioning
confidence: 99%
“…18 On these days, myocardial infarction and major arrhythmia admissions increased 3 times compared to the same day in previous years ( Figure 3). The highest incidence of cardiac events occurred during the first two hours of the games.…”
Section: Acute Stress and Cardiovascular Diseasementioning
confidence: 81%